Fungsi Rebab Dalam Penyajian Karawitan Sunda - Rian Permana (JPKS (Jurnal Pendidikan dan Kajian Seni), 2019)
Abstract : This research and study aims to determine the extent of the role of the fiddle in the presentation of Sundanese musicians, both the function of the fiddle with sekar or sekar gending. It is hoped that this research and study can provide useful information about how a rebab interpreter should work when performing Sundanese musical performances. This needs to be understood as a basis for understanding, especially for a trigger, so that the appearance of his performance can be enjoyed in harmony, in rhythm, one taste, and one accord in one Sundanese musical dish. Abstrak : Penelitian dan kajian  ini bertujuan untuk mengetahui sejauhmana peranan rebab dalam penyajian karawitan Sunda, baik secara fungsi rebab dengan sekar maupun sekar gending. Diharapkan penelitian dan pengkajian ini dapat memberikan manfaat informasi tentang bagaimana semestinya garap seorang juru rebab ketika melakukan sajian karawitan Sunda. Hal ini perlu dipahami sebagai dasar pemahamn khususnya bagi seorang juru rebab agar sajian penampilannya dapat terasa dinikmati selaras, seirama, satu rasa, dan sehati pada satu garapan sajian karawitan Sunda.